Bestari Partners - Hitapriya Suprayitno (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2019)
PAPER WRITTING STIPULATION Papers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows. - Papers must be a real work of the author. - Papers has never been published in other media. - Papers contain discussion about Infrastructure & Facility Asset Management. - Papers contains a new discussion, judging based on the discussion that has been published on JIFAM. - The paper have to take a reference from JIFAM/JMAIF for at least 1 paper and from outside JIFAM a minimum of 1 paper. - Paper lengths are limited in 8-16 pages. - Paper writing format can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifam. TOPIC SCOPE JIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited, of the following. - I & F Function - I & F Demand - Supply - I & F User Behavior - I & F Policy - I & F Planning - I & F Administration Aspects - I & F Operation System - I & F Maintenance System - I & F Evaluation Technique - I & F Disposal - I & F Economical Aspect - I & F Financial Aspect - I & F Management Organization - I & F Spatial Aspects and Environmental Aspects REVIEWER Hitapriya Suprayitno, Institut Teknologi Sepuluh Nopember (ITS), Surabaya. Ria Asih Aryani Soemitro, Institut Teknologi Sepuluh Nopember (ITS), Surabaya. Data Iranata, Institut Teknologi Sepuluh Nopember (ITS), Surabaya.